500 participants took part in UMP Charity Run for Palu Humanitarian Mission fund - Siti Nur Azwin, Zulkapri (2019)
The Department of Student Affairs & Alumni (JHEPA), Universiti Malaysia Pahang (UMP) organised a charity run in a move to raise funds for the Palu Humanitarian Mission in Indonesia which was badly hit by natural disaster.